Economical energy allocation for the landward invasion of Spartina alterniflora in estuaries in the Yellow River Delta, east China. (February 2023) - Liu, Jiakai; Yan, Guoxin; Pan, Yueyan; Zhang, Zhenming; Chen, Yinglong; Zhang, Mingxiang
Highlights: The morphology resistance to waves of invasive S.alterniflora is higher than native P.australis. P. australis allocate excessive energy during stem growth, thereby decreasing reproduction and fitness . Economic energy allocation contributed to the successful invasion of S. alterniflora. Abstract: Smooth cordgrass ( Spartina alterniflora ) introduced to China in 1970 s for coastline stabilization threatening the habitat range of native Phragmites australis and even become more adaptive than P. australis. Thus, we used electronic universal testing machine and Van Soest method to compare the morphological and biomechanical responses of these two species to wave interference in the Yellow River Delta, east China. Our study showed that the morphological response of P. australis was more sensitive to waves with shorter individuals in wave zones but larger stem diameter and higher biomass than those in none-wave zones, while S. alterniflora did not exhibit such variations. In wave zones, S. alterniflora invaded P. australis ' habitat regardless higher stem-bending resistance of P. australis with excessive energy allocated in stem growth while decreasing reproduction and fitness. Compared with the none-wave zones, S. alterniflora allocated excessive energy in the stem to resist wind interference, and they are less fitted than P. australis . Thus, economic energy allocation to wave mechanical interference contributed to the successful invasion of S. alterniflora to landward in estuaries. S. alterniflora continued to expand landward in a semi-saline area but the community pattern may maintain the status quo for areas with low salinity and high wave interference.